Selitrichodes neseri n. sp., a new parasitoid of the eucalyptus gall wasp Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae: Tetrastichinae) - Kelly, Janine; la Salle, John; Harney, Marlene; Dittrich-Schröder, Gudrun; Hurley, Brett (Zootaxa, 2012)
Selitrichodes neseri Kelly & La Salle n. sp. (Hymenoptera: Eulophidae: Tetrastichinae), is described as a parasitoid of the inva-sive eucalyptus gall wasp Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae: Tetrastichinae), which is causingsubstantial damage particularly in commercial Eucalyptus plantations. Selitrichodes neseri was originally collected in Australiain 2010 when searching for biological control agents of L. invasa. It has since been reared in quarantine in South Africa where it is being evaluated for release as a biological control agent of L. invasa.